Свинцеві фігурки скіфських вершників із Ольвії - Хмелевський, Д.М. (Археологія, 2024)
Мета статті — розглянути окрему категорію свинцевих виробів із розкопок Ольвії; на їх прикладі дослідити технологічні особливості виготовлення таких виробів і зв’язок Ольвії з варварським оточенням. Ідеться про невелику групу композиційних фігурок, які за деталями одягу можна вважати зображенням скіфських вершників. In the article, the author aims to examine a specific category of lead artefacts discovered in Olbia, with a focus on investigating the technological features of their production and Olbia’s connections with its barbarian surroundings. The research employs an interdisciplinary approach utilising methods of analysis, synthesis, and socialisation, particularly emphasising the comparativehistorical method. Against the backdrop of extensive studies on metalworking in Olbia, especially in foundries and blacksmithing, the processing of lead and the production of artefacts from it remain relatively under-explored. Therefore, this article delves into one category of items made of this metal. A distinct group of composite figurines and their fragments — statuettes of riders on stationary standing horses is explored in the article. Based on the details of their attire, they can be identified as Scythian horsemen, raising questions about Olbia’s connection with its barbarian environment. According to the classification of K. I. Zaitseva, in addition to riders on stationary standing horses, there is a small number of figurines depicting horsemen on galloping horses. All examined lead figurines are cast in the technique of either single- or double-sided relief, indicating their different usage. If double-sided statuettes could be used autonomously, single-sided ones may have needed to be attached to some surface. The presented depictions of Scythian riders not only provide insights into the production of various lead items in Olbia, but also raise questions about Greek-barbarian contacts, possibly indicating the residence of local inhabitants in Olbia and their status in both the city and barbarian interactions. They also expand our understanding of Scythian attire and horsemen. Lead items originating from Olbia can be categorised into several groups depending on their purpose. Primarily, these are household items (clamps, spindle whorls, fishing weights). During the Hellenistic period, handles (clamps) for wooden coffins (biers) were manufactured. However, the most interesting group comprises votive items, with around 350 known examples to date. These include bucrania, stylised sheep heads, and labryses. A smaller group consists of anthropomorphic figurines of gods, warriors, chariots, plaques with narrative scenes (sacrifices) and riders. Such votive figurines are found in mounds and tombs as burial offerings. Less frequently, they are found directly within burials. Additionally, they may have been used in religious rituals and in decorating household altars. The question of the ownership of such statuettes remains unanswered. However, Herodotus wrote about a barbarian population known as Callipidae or Hellenes-Scythians in the territory of the Olbian state. It is essential to note that in the 4th century BC, coins were minted in Olbia bearing the image of the Scythian king Ateas, and Scythian weaponry was commonly depicted on the Bosporus, indicating traditional Scythian-Hellenic relations that likely solidified after the Scythians defeated Zopyrion’s army under the walls of Olbia. Thus, the presence of residents in the city cannot be denied.